(untitled) (Research, Society and Development, 2021)
This is a case report, developed by two nursing students from an institution located in the interior of the state of Rio Grande do Sul / Brazil. The objective of the study is to discuss the Nursing Care Systematization (SAE) applied to a patient with a medical diagnosis of Spine Fracture in L3. The work was carried out in the discipline of Nursing in adult and elderly health, during the first semester of 2020. After collecting data and listening to the patient, nursing diagnoses were elaborated using the NANDA taxonomy and nursing interventions. through the NIC, aiming to contribute to the patient’s professional practice and prognosis, with the aim of providing improvement in the patient’s quality of life and well-being through nursing actions and interventions. After conducting the case study and experience of the academics, it is possible to conclude the importance of the application of SAE, which aims to achieve the improvement of the patient’s clinical condition, through interventions, each with its importance.